Asymmetry parameter for the nonmesonic decay of 5LHe - Barbero, Cesar [UNESP]; Galeao, Alfredo Pio Noronha Rodrigues [UNESP]; Krmpoti, Francisco [UNESP] (Sociedade Brasileira de Física, 2004)
We report the preliminary result of an exact calculation of the asymmetry parameter, alambda, in the nonmesonic hypernuclear decay, based on a one-meson-exchange (OME) model. For the case of He and including one-pion-exchange only, the result is shown not to differ considerably from the one obtained with the approximate formula widely used in the literature. In particular, the sign of alambda remains negative, in disagreement with its most recent experimental determination. Whether these facts remain true for heavier hypernuclei and in a more complete OME model is still under investigation.